2017
DOI: 10.1371/journal.pone.0187395
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac cycle-synchronized electrical muscle stimulator for lower limb training with the potential to reduce the heart's pumping workload

Abstract: BackgroundThe lower limb muscle may play an important role in decreasing the heart’s pumping workload. Aging and inactivity cause atrophy and weakness of the muscle, leading to a loss of the heart-assisting role. An electrical lower limb muscle stimulator can prevent atrophy and weakness more effectively than conventional resistance training; however, it has been reported to increase the heart’s pumping workload in some situations. Therefore, more effective tools should be developed.MethodsWe newly developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The muscles in the lower limbs, for example, help propel deoxygenated blood towards the heart and assist in the dilation and filling of capillaries, thereby enhancing cardiac pumping capacity. Therefore, sarcopenia and muscle weakness caused by hyperthyroidism may increase the workload on the heart and worsen the condition of cardiovascular diseases ( 19 ). Additionally, another study has shown that treatment methods involving electrical stimulation of the lower limbs to induce muscle contractions can effectively improve flow-mediated dilation in patients with chronic heart failure ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The muscles in the lower limbs, for example, help propel deoxygenated blood towards the heart and assist in the dilation and filling of capillaries, thereby enhancing cardiac pumping capacity. Therefore, sarcopenia and muscle weakness caused by hyperthyroidism may increase the workload on the heart and worsen the condition of cardiovascular diseases ( 19 ). Additionally, another study has shown that treatment methods involving electrical stimulation of the lower limbs to induce muscle contractions can effectively improve flow-mediated dilation in patients with chronic heart failure ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The muscles in the lower limbs, for example, help propel deoxygenated blood towards the heart and assist in the dilation and filling of capillaries, thereby enhancing cardiac pumping capacity. Therefore, sarcopenia and muscle weakness caused by hyperthyroidism may increase the workload on the heart and worsen the condition of cardiovascular diseases (19).…”
Section: Discussionmentioning
confidence: 99%